The Effect of Mating Ratio on Guinea Fowl Reproductive Performance - Joseph Atawalna; Richard K Agbehadzi; Daniel Cobbinah Junior Essel; Patrick Mensah (SVU-International Journal of Veterinary Sciences, 2022)
A study was conducted to investigate the effect of mating ratio on Guinea fowl reproductive performance. A total of 420 Guinea fowls of the pearl variety were randomly selected from growers housed on the farm. The selected birds were sexed and assigned to three treatment groups according to a mating ratio of 1:4, 1:6 and 1: 10 respectively, with a maximum of 120 female Guinea fowls in each group. Eggs were collected daily from the laying birds by treatment groups, graded and stored for a maximum of seven days at room temperature. The selected eggs were fumigated and incubated using an automated Petersime incubator. Percent fertility, hatchability and embryonic mortality were measured after 28 days of incubation. The fertility rate (%) was 84 ± 3.4, 78 ± 3.9 and 75 ±5.1 in Guinea fowls with mating ratios 1:4, 1:6 and 1:10, respectively. The fertile hatchability and total hatchability rates (%) were 66 ± 3.3, 55 ±3.7, 59 ± 28, 47 ± 24 and 51 ± 35, 39 ±28 respectively in Guinea fowls with mating ratios 1:4, 1:6 and 1:10 As mating ratio increased from to 1:4, 1:6 and 1:10, embryonic mortality rates (%) were 34 ±3.3, 41 ± 28 and 49 ± 35, while percentage viable keets were 98 ± 0.72, 96 ± 2.5 and 96 ± 2.0. Mating ratios did not significantly affect reproductive performance. The mating ratio of one male Guinea fowl to four males was optimal for reproduction.